2020
DOI: 10.13189/ujer.2020.080301
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Math Anxiety and Perception of the Utility of Geometry in Primary Education in Prospective Teachers

Abstract: Math Anxiety not only plays an important role in the academic performance of students but also has a significant influence on the methodology adopted by teachers. In this study, we examine the relationship between the levels of Math Anxiety of a group of prospective teachers and their opinions about the importance of Geometry in Primary Education. Abbreviated Math Anxiety Scale (AMAS) was applied to 152 students of the Primary Education Degree, along with open-ended questions on their opinions about the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…A study of prospective teachers by Gutiérrez-Rubio et al (2020) found that the main perceived learning goals when teaching geometry in school were procedural (instrumental in Skempian terms (Skemp, 1978)), focussing only on making further progress in geometry (identifying shapes, calculating areas etc.) rather than relational and general (improved mathematical reasoning, everyday problem solving etc.).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A study of prospective teachers by Gutiérrez-Rubio et al (2020) found that the main perceived learning goals when teaching geometry in school were procedural (instrumental in Skempian terms (Skemp, 1978)), focussing only on making further progress in geometry (identifying shapes, calculating areas etc.) rather than relational and general (improved mathematical reasoning, everyday problem solving etc.).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, this method could improve a better understanding of the mean for learning math (Dan et al, 2020). On the basis of students' ability to apply knowledge to real situations, we want to test the effectiveness of the process of designing and applying geometry teaching (Gutiérrez-Rubio et al, 2020;Matiash & Mykhailenko, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the authors [5], [6], [7], [8], [9]) point out that the nature of teachers' beliefs about this and the teaching and learning can also play an important role in shaping their teaching activities. According to many experts, exploring the ways in which high school math teachers bring new meaning to the development of general education [37,38,39,40], Tran Viet Cuong said that learning and life are not separate; recently teachers need to guide students how to learn and how to handle situations in real contexts [41].…”
Section: Introductionmentioning
confidence: 99%